PERAN NILAI-NILAI PANCASILA SEBAGAI PEDOMAN DALAM PEMBENTUKAN KARAKTER GENERASI MUDA - Afifah, Qistin; Najicha, Fatma Ulfatun (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2022)
Character and morals are attitudes or traits that must be owned by the younger generation. With the good character and morality of the younger generation, it will give birth to a nation and state that is of good quality and quality. The success and progress of a nation or country cannot be separated from the involvement of its people, especially the younger generation. So that the younger generation needs to equip themselves with character and morals that implement Pancasila values in them. The younger generation must make Pancasila a way of life which includes the basic concept of life that the nation aspires to. A view of life is embodied in human thoughts and ideas about the existence of life which is considered good which will bring a nation to be better.